IBM DB2 11 for z/OS technical overview - Bruni, Paolo (IBM redbooks., 2013)
IBM DB2 Version 11.1 for z/OS is the fifteenth release of DB2 for IBM MVS. This IBM Redbooks publication introduces the enhancements made available with DB2 11 for z/OS. It helps database administrators to understand the new functions and performance enhancements, to plan for ways to use the key new capabilities, and to justify the investment in installing or migrating to DB2 11. Coverage includes: performance and synergy with the IBM System z hardware; reliability, availability, and scalability; savings in money and time; new installations of DB2; simpler, faster migration from DB2 10 for z/OS subsystems; enhanced business analytics. --